The Prognostic Value of Cardiopulmonary Exercise Testing in Idiopathic Pulmonary Fibrosis - Fell, Charlene D. (American Thoracic Society, 2009)
Rationale: Idiopathic pulmonary fibrosis (IPF) is characterized by progressive dyspnea, impaired gas exchange, and ultimate mortality. Objectives: To test the hypothesis that maximal oxygen uptake during cardiopulmonary exercise testing at baseline and with short-term longitudinal measures would predict mortality in patients with idiopathic pulmonary fibrosis. Methods: Data from 117 patients with IPF and longitudinal cardiopulmonary exercise tests were examined retrospectively. Survival was calculated from the date of the first cardiopulmonary exercise test. Measurements and Main Results: Patients with baseline maximal oxygen uptake less than 8.3 ml/kg/min had an increased risk of death (n = 8; hazard ratio, 3.24; 95% confidence interval, 1.10–9.56; P = 0.03) after adjusting for age, gender, smoking status, baseline forced vital capacity, and baseline diffusion capacity for carbon monoxide. We were unable to define a unit change in maximal oxygen uptake that predicted survival in our cohort. Conclusions: We conclude that a threshold maximal oxygen uptake of 8.3 ml/kg/min during cardiopulmonary exercise testing at baseline adds prognostic information for patients with IPF.